2022
DOI: 10.1098/rspb.2022.1947
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary megafauna extinctions altered body size distribution in tortoises

Abstract: The late Quaternary is characterized by the extinction of many terrestrial megafauna, which included tortoises (Family: Testudinidae). However, limited information is available on how extinction shaped the phenotype of surviving taxa. Here, based on a global dataset of straight carapace length, we investigate the temporal variation, spatial distribution and evolution of tortoise body size over the past 23 million years, thereby capturing the effects of Quaternary extinctions in this clade. We found a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…The Eocene–Oligocene witnessed a peak of diversity, related to the origin of crown‐group Testudinidae (Lourenço et al, 2012 ; Vlachos & Rabi, 2018 ), after which the group spread from Eurasia to most of the world. Therefore, the recent high variation in body size within tortoises might be also related to the expansion of occupied habitats (as in freshwater turtles), also associated with specific diversification and extinction dynamics within the group (e.g., Joos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Eocene–Oligocene witnessed a peak of diversity, related to the origin of crown‐group Testudinidae (Lourenço et al, 2012 ; Vlachos & Rabi, 2018 ), after which the group spread from Eurasia to most of the world. Therefore, the recent high variation in body size within tortoises might be also related to the expansion of occupied habitats (as in freshwater turtles), also associated with specific diversification and extinction dynamics within the group (e.g., Joos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence indicated that podocnemidids attained gigantic sizes (SCL > 150 cm [ 3 ]) at least twice: Late Palaeocene [ 33 , 34 ] and Miocene [ 6 , 35 ]. This is consistent with the periods in which extreme sizes evolved in other groups of turtles [ 5 ], as well as in other reptiles, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Titanochelon schaefferi and Megalochelys atlas [ 32 ]). Furthermore, those giant reptiles seem to have disappeared after 50–40 kyr ago [ 40 ], with testudinids showing body size decrease by the end of the Pleistocene [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations